Bid-Ask Spreads and Trading Activity in the S&P 100 Index Options Market - George, Thomas J.; Longstaff, Francis A. (Journal of Financial and Quantitative Analysis, 1993)
Thomas J. George, Francis A. Longstaff, Bid-Ask Spreads and Trading Activity in the S&P 100 Index Options Market, The Journal of Financial and Quantitative Analysis, Vol. 28, No. 3 (Sep., 1993), pp. 381-397